2003
DOI: 10.1023/a:1021887100216
|View full text |Cite
|
Sign up to set email alerts
|

FosB is Highly Expressed in Normal Mammary Epithelia, but Down-Regulated in Poorly Differentiated Breast Carcinomas

Abstract: FosB is a member of the AP-1 family of transcription factors which represent important regulators of cell proliferation and differentiation. Based on prior results which indicated a role of FosB in breast cancer, we studied FosB protein and mRNA expression by immunohistochemistry and, partly, in situ hybridization in 68 mammary carcinomas and normal breast tissues. We found strong nuclear FosB immunoreactivity in epithelial cells of normal lobules and ducts, whereas carcinomas frequently showed loss of FosB ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 33 publications
7
29
0
1
Order By: Relevance
“…Our own prior investigations have shown that FosB is highly expressed in more differentiated, hormone-receptor-positive tumours (Milde-Langosch et al, 2003). Thus, the comparison of p-ERK expression with AP-1 protein results confirms our conclusion that overexpression of these activated MAP kinases is associated with a better prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…Our own prior investigations have shown that FosB is highly expressed in more differentiated, hormone-receptor-positive tumours (Milde-Langosch et al, 2003). Thus, the comparison of p-ERK expression with AP-1 protein results confirms our conclusion that overexpression of these activated MAP kinases is associated with a better prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…In normal lobular and ducts, the epithelial cells show higher expression of FosB mRNA and protein, whereas in majority of carcinomas and MCF-7 cells less of FosB protein was expressed [40], and this is in agreement with our study using A549 cells where little or no FosB mRNA expression was observed.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, FosB, which may be involved in changing mammary epithelial cells into poorly differentiated breast cancer cells (Milde-Langosch et al, 2003), has been suggested to be one of the molecular targets of cell death signaling stimulated by (-)-xanthatin (Fig. 4), and (-)-xanthatin may also have multiple action points to attack cancer cells, indicating its potential as a lead com- A working model of (-)-xanthatin-mediated cell death is described in combination with a previous study (Milde-Langosch et al, 2003).…”
Section: Resultsmentioning
confidence: 72%
“…4), and (-)-xanthatin may also have multiple action points to attack cancer cells, indicating its potential as a lead com- A working model of (-)-xanthatin-mediated cell death is described in combination with a previous study (Milde-Langosch et al, 2003). As shown in the Figure, (-)-xanthatin may evoke cell death through the up-regulation of FosB, which is down-regulated in poorly differentiated breast cancer cells (MildeLangosch et al, 2003).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation